PENYELESAIAN KONFLIK PERBATASAN INDONESIA-TIMOR LESTE DALAM KONTEKS POLITIK TATA RUANG - Yohanes Arman; Junaldo Klau, Kaldianus Uruk (JOURNAL OF LAW AND NATION, 2024)
The border space as a development resource has a strategic position, because space is a place where the natural resources are at once as a container where the various activities. Various activities that take place in a space generally are social, political, and economic activities that have unequal economic limitations and opportunities. The limitations and inequalities in these occasions often have a positive or negative impact on other activities, or in other words space has the potential to create disagreements between the activities of one sector and the other. Henri Lefebvre asserts that there are three sets of concepts of how a social space is produced, namely: spatial practice, spatial representation and space of repression. All interested parties will continue to seek to dominate the use or utilization of a space and reproduce all the knowledge to maintain their hegemony over the use of the space. In other words, the common space will always adjust the interests of capital in order to guarantee the relations or production and reproduction that are capitalistic. Using descriptive-qualitative research methods, this study shows that conflict resolution at the border has not prioritized the existing social ethics in border areas and the government often negates local forces in the border areas. Using descriptive-qualitative research methods, this study shows that conflict resolution at the border has not prioritized the existing social ethics in border areas and the government often negates local forces in the border areas.